To the problem of building a mathematical model of one-dimensional object - Бойко, Тетяна Владиславівна; Абрамова, Алла Олександрівна; Серебрянський, Дмитро Олександрович; Семенюк, Микола Віталійович (Technology audit and production reserves, 2015)
Methods of mathematical modeling of one-dimensional object using the method of least squares approximation and Chebyshev polynomials are investigated. Object is eight-stage centrifugal filter. The aim of the article is the building the mathematical relationship of aerodynamic drag depending on the gas flow. Approximating procedures of polynomial coefficients determination and calculation of residual variance in the system of Mathcad are developed. The influence of the degree of the polynomial degree on the accuracy of the results is analyzed. The obtained values of the residual variance indicate coincidence of results using both methods. From obtained results it can be argued that the investigated approximation methods give the same results, and to build approximating polynomial for the communication of parameters for input and output of object can be used both methods. If compared in terms of simplicity of constructing an algorithm method of least squares is simplest for implementation.